Silver diamine fluoride treatment of active root caries lesions in older adults: A case series. (February 2021) - Mitchell, Chelsea; Gross, Andrew J; Milgrom, Peter; Mancl, Lloyd; Prince, David B
Abstract: Objective: The authors conducted a case series to determine arrest of root surface caries lesions in older adults when teeth were treated topically with 38 % silver diamine fluoride (SDF). Methods: The study was a prospective, single center case series. The patients were 62 older adults (age ≥55 years) who sought treatment at a dental school clinic. To be included, a patient needed to have at least one active root caries lesion. Lesions were rinsed and then dried with air, isolated, and then 38 % SDF was applied for two minutes with a microbrush. Treated lesions were re-evaluated at 2–3 weeks. Treatment was repeated every six months. Survival analysis methods for clustered data were used to estimate the caries lesion arrest probability over time separately for root surfaces and at crown margins. Results: Fifty-five participants returned for follow-up (44 % female, mean age (SD) 79.8 (7.4)). The probability of a lesion arresting with treatment ranged from 82.9 to 91.6%. Arrest rates at 18 months were slightly higher in root surfaces than around crown margins, 91.6 % (95 % CI 69.1–97.1) versus 89.8 % (95 % CI 71.6–96.3). All furcal lesions (n = 7) were arrested by 6 months, 100 % (95 % CI 59–100). Conclusion and Clinical Significance: Repeated application of 38 % SDF at 6-month intervals was effective in arresting decay of root surface lesions and lesions around crowns in older adults. Study outcomes support SDF treatment for older adult patients who are frail and residing in nursing homes or dependent living facilities.